2021
DOI: 10.48550/arxiv.2105.03287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Order in the Court: Explainable AI Methods Prone to Disagreement

Abstract: In Natural Language Processing, featureadditive explanation methods quantify the independent contribution of each input token towards a model's decision. By computing the rank correlation between attention weights and the scores produced by a small sample of these methods, previous analyses have sought to either invalidate or support the role of attentionbased explanations as a faithful and plausible measure of salience. To investigate what measures of rank correlation can reliably conclude, we comprehensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Specialized XAI techniques even exist for adaptive systems such as interactive visualization systems [77], interactive virtual agents [37,83], active learning [27], and human-in-the-loop systems [86] . Furthermore, comparative studies across multiple XAI techniques have shown low mutual agreement [58], which is consistent with internal research findings at AI Research. With these research findings taken together, we expect that different explanation tools will be needed to address each problem domain effectively.…”
Section: The Challengessupporting
confidence: 79%
“…Specialized XAI techniques even exist for adaptive systems such as interactive visualization systems [77], interactive virtual agents [37,83], active learning [27], and human-in-the-loop systems [86] . Furthermore, comparative studies across multiple XAI techniques have shown low mutual agreement [58], which is consistent with internal research findings at AI Research. With these research findings taken together, we expect that different explanation tools will be needed to address each problem domain effectively.…”
Section: The Challengessupporting
confidence: 79%
“…50 per class). Subsequent experiments are performed on all validation images or a subset thereof 3 . Hyper-parameters are tuned on validation data as well, as we assume an attacker as well as people looking for explanations have access to the respective data.…”
Section: Datamentioning
confidence: 99%
“…This lack of standard evaluation metrics hinders a comparison between different explanation techniques. Even worse, it was shown that different explanation methods disagree [3,4], which suggests that at least some of them do not capture the real inner workings of a system and that explanations produced by an explainer A cannot serve as a ground truth for a newly developed explainer B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neely et al (2021) compare DistilBERT based models, we compare BERT-based models. They further constrain their evaluation to 500 instances while we are calculating the values for the entire datasets.…”
mentioning
confidence: 99%